Rancang Bangun Sistem Antrian Pengambilan Kamera Di Logistik Trans7 Secara Jarak Jauh Dengan Bantuan Short Message Service Berbasis Visual Basic 6 - Kusumo Putro, R.A. Suwodjo; Azman, Novi; Darmawan, Benny (Jurnal Ilmiah Giga, 2013)
ABSTRACT. Its quite difficult to take the camera for each trans7 cameraman, in the Logistic Area of Trans7. After taking queueing number, the cameraman will have to wait for a quite long time until finally he got the camera. So did the logistic staff, they also having problem in distributing the camera to the related cameraman. To solve the problem, the short message service is one of the alternate option, which arrange the queue and to call the related cameraman. This system consists of Netbook as a database center and data processing, C55 cellphone as the message transmitter and receiver and active speaker to call each cameraman. This system can accept queueing request manually in logistic area and also accomodate each camera wanted by each cameraman that requested by sms. The benefits of this system for logistics are it can directly autosave the data of the cameraman including the borrowed camera, calling the number of queue and delaying the process for the unresponsive cameraman. The system always re-check staffs ID and the sms received number as validation. Keywords : waiting list Camera shooting, SMS (Short message service), Visual basic